Siri'na Pacce: a Form of Fulfilling Women's Rights through the Conduct of Responsible Fisheries - Yulia Yulia; Baso Madiong; Mustawa Mustawa; Ruslan Renggong; Zulkifli Zulkifli (Universitas Negeri Gorontalo, 2023)
Conservation of fish resources aims to protect fish species, maintain fish species diversity, protect ecosystems, and utilize fish resources in a sustainable manner. This study aims to analyze the legal protection of women's empowerment in the conservation of fish resources with the siri'na pacce philosophy of the Makasssar tribe. This study uses a qualitative approach, which is elaborated by using legal norms based on the provisions of international law and national law. The results of this study show that women's empowerment in the conservation of fish resources is protected by international and national laws, so that women in Takalar Regency, South Sulawesi, are entitled to legal protection from misbehavior. discriminatory on any basis, to empower instilling children and families' care in conserving fish resources with the Siri'Na Pacce philosophy of not doing Siri' Mappakasiri'siri' which can prevent someone from doing things that are contrary to the law, norms that live in society, and other things that can harm humans and humanity itself, especially in the protection, utilization, and conservation of fish resources.